Field practices for wastewater use in agriculture : future trends, and use of biological systems - Tripathi, Vinod K.; Goyal, Megh R. (Florida Apple Academic, 2021)
"Field Practices for Wastewater Use in Agriculture: Emerging Issues, Future Trends, and Use of Biological Systems discusses the growing importance of wastewater application in the field of agriculture. Addressing the tremendous need for the irrigation sector to reduce the demand for freshwater in agriculture, this volume looks at wastewater as a source for agricultural irrigation. The volume is divided into four sections: current and emerging issues in wastewater use in agriculture, wastewater management with biological systems, effective field practices for wastewater use, and case studies that provide information on scientific analytical studies on the environment under the influence of wastewater quality from different pollution sources. This book sheds light on the vast potential of wastewater use in agricultural irrigation while also considering safety of the agricultural products for human consumption. Much emphasis has also been given to technological aspects for the treatment of wastewater to protect our environment for better public health protection. Key features: Provides information to planners and policymakers through case studies Offers solutions for the treatment of wastewater generated from different sources Considers sustainability issues and the protection of the environment Examines the issue of water quality from certain sources and with specific techniques"--
Keywords: Sewage--irrigation.; Sewage--Purification.; Sustainable--agriculture; Biotechnology